2021
DOI: 10.1016/j.cemconres.2021.106513
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polycarboxylate superplasticizer, citric acid and their combination on the hydration and workability of calcium sulfoaluminate cement

Abstract: PCEs are well known to improve the initial fluidity of CSA. However, their dispersion efficiency drops quickly over time. This issue can be solved by incorporating retarders. In this context, this paper deals with the influence of citric acid, used as a retarder, PCE and their combination on the hydration and workability of CSA. Isothermal calorimetry, XRD and TG analysis were used to describe the hydration process, while workability was characterized with the mini-cone test. Adsorption behavior was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…The addition of PS allowed UHPG to maintain a slump-flow of 215 mm with only about 33% loss of slump-flow after 60 min. The results confirmed that UHPG outperformed the initial slump-flow of other UHPCs [17,18,[29][30][31]. The best rheological behavior was achieved with a PS dosage of 0.93% of the binders in this study.…”
Section: Slump-flow Testsupporting
confidence: 81%
See 1 more Smart Citation
“…The addition of PS allowed UHPG to maintain a slump-flow of 215 mm with only about 33% loss of slump-flow after 60 min. The results confirmed that UHPG outperformed the initial slump-flow of other UHPCs [17,18,[29][30][31]. The best rheological behavior was achieved with a PS dosage of 0.93% of the binders in this study.…”
Section: Slump-flow Testsupporting
confidence: 81%
“…As a result, PS plays an important role in the flow behavior of UHPG. As mentioned in previous studies [17,18,31], the PS exhibited better fluidity properties and delayed the process of hydration. The addition of PS allowed UHPG to maintain a slump-flow of 215 mm with only about 33% loss of slump-flow after 60 min.…”
Section: Slump-flow Testsupporting
confidence: 69%
“…Several authors mention that retarders tend to form complexes with calcium ions. These complexes, being small and highly charged, adsorb first onto the surface of cement particles and partially hinder the adsorption of the PCE [6,8,9]. The aim of this study is to investigate the effect of the combination of three different retarders (citric acid, tartaric acid and potassium gluconate) with PCE on hydration and rheology of CSA.…”
Section: C4a3$ + 18h → C4a$h12 + 2ah3mentioning
confidence: 99%
“…As another important category of admixture, the retarders has been used to regulate the setting behaviours in a cementitious system with fast hydration [ 43 , 44 , 45 ]. To achieve multiple performances in adjusting the properties of cement, the retarders are often combined with the PCEs in a Portland cement-based system or those novel cementitious systems [ 46 , 47 ]. However, in cementitious system with clays, the combination of PCE with retards has not been extensively research.…”
Section: Introductionmentioning
confidence: 99%